Association of length of service and job category with occupational health literacy of port employees in Shenzhen, China - Jinlin Wang; Chunbao Mo; Qiujie Sheng; Yuehong Huang; Dafeng Lin; Yuan Liang; Naixing Zhang (BMC, 2023)
Abstract Background Health literacy (HL) is associated with health outcomes, but little is known about the occupational HL (OHL) for port employees and its link to the length of service and job category. Method A cross-sectional survey was conducted on 3492 port employees from the Occupational Health Survey for Port Employees project, and a special questionnaire was utilized to measure the OHL status. Binary and ordinal logistic regressions were used to estimate the association. Result Among the participants, 72.90% had sufficient OHL with a mean score (standard deviation) of 53.10 (7.26). Binary logistic regression results indicated that the association between length of service (33-40 years group Adjusted OR = 1.11; 41-49 years group Adjusted OR = 1.14; ≥50 years group Adjusted OR = 1.19) and job category (longshoremen Adjusted OR = 0.90; driver Adjusted OR = 0.91) with OHL were statistically significant. Ordinal logistic regression results indicated that, for OHL, Adjusted OR was increased in different lengths of service level (33-40 years group, Adjusted OR = 1.50; 41-49 years group, Adjusted OR = 1.75; ≥50 years group, Adjusted OR = 2.19), and the Adjusted OR of skilled workers was 1.60. Conclusion Most port participants had sufficient OHL, and the length of service and job category could affect OHL. The effect of the length of service may be more obvious; the length of service can promote the improvement of OHL continuously.